Improving rate performance of high-voltage spinel cathode by changing structural evolution from two-phase to solid-solution reactions. (10th August 2018) - Xue, Yuan; Han, Yi; Yu, Hao-Xiang; Shu, Jie; Wang, Zhen-Bo; Zheng, Li-Li; Xia, Yun-Fei
Abstract: The Ni/Mn ratios are changed to improve rate performance of high-voltage spinel. LiNi0.5 Mn1.5 O4 and LiNi0.4 Mn1.6 O4 with annealed treatment are prepared. The structural evolutions during delithiation/lithiation are studied by in-situ XRD technique. It is found that the decrease of Ni/Mn ratios can change the structural evolutions from two-phase transformations to solid-solution reaction. The variations of electronic conductivity and lithium diffusivity during discharge are calculated by the galvanostatic intermittent titration technique. LiNi0.5 Mn1.5 O4 and LiNi0.4 Mn1.6 O4 have similar electronic conductivity and different lithium diffusivity. Lithium diffusion coefficients of LiNi0.5 Mn1.5 O4 with two-phase transformations are low due to limited lithium diffusion across the interface between two phases. For LiNi0.4 Mn1.6 O4, the single phase solid-solution reaction is beneficial to lithium diffusion. Attributed to higher lithium diffusivity, the rate performance of LiNi0.4 Mn1.6 O4 is obviously improved.